2021
DOI: 10.18488/journal.73.2021.93.237.249
|View full text |Cite
|
Sign up to set email alerts
|

Is Working from Home Good for Work-Life Balance, Stress, and Productivity, or does it Cause Problems?

Abstract: This study aims to investigate the impact of employee productivity while working from home for a long period due to the COVID-19 pandemic quantitatively from the aspects of work-life balance, and employee stress levels. Several previous studies have explained that working from home (WFH) is known to contribute positively to work productivity. However, in contrast, several other studies have shown that working from home harms employee productivity. This research was conducted in Jakarta, Indonesia. The study sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(53 reference statements)
2
7
0
Order By: Relevance
“… Green Leadership challenges and mental health outcomes Crisis management ( Appelgren, 2022 ), ( Stoker et al, 2022 ) 16 Journalism Studies Journal of Leadership and Organizational Studies Journal of International Women's Studies Frontiers in Education International Journal of Sexual Health Mental health ( Subha, R, & Thomas, 2021 ), ( Zapata-Garibay et al, 2021 ), ( Prabowo et al, 2022 ) Yellow Work-related outcomes Work engagement ( Palumbo, 2020 ), ( Albro & McElfresh, 2021 ; Negi, Pant, & Kishor, 2021 ), ( Mehta, 2021 ). ( Negi et al, 2021 ) 263 International Journal of Public Sector Management Journal of Academic Librarianship Transnational Marketing Journal Journal of Public Affairs Sustainability (Switzerland) Organizational Dynamics Indian Journal of Forensic Medicine and Toxicology Journal of International Women's Studies International Journal of Disaster Risk Reduction Humanities and Social Sciences Letters Asian Social Work and Policy Review Work stress ( Molino et al, 2020 ), ( George, Atwater, Maneethai, & Madera, 2022 ), ( Joshi et al, 2020 ), ( Wiradendi Wolor et al, 2021 ), ( Subha et al, 2021 ; Syed et al, 2021 ) Work-life balance ( Wiradendi Wolor et al, 2021 ), ( Palumbo, 2020 ), ( Jasrotia & Meena, 2021 ), ( Subha et al, 2021 ) Purple ...…”
Section: Results and Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“… Green Leadership challenges and mental health outcomes Crisis management ( Appelgren, 2022 ), ( Stoker et al, 2022 ) 16 Journalism Studies Journal of Leadership and Organizational Studies Journal of International Women's Studies Frontiers in Education International Journal of Sexual Health Mental health ( Subha, R, & Thomas, 2021 ), ( Zapata-Garibay et al, 2021 ), ( Prabowo et al, 2022 ) Yellow Work-related outcomes Work engagement ( Palumbo, 2020 ), ( Albro & McElfresh, 2021 ; Negi, Pant, & Kishor, 2021 ), ( Mehta, 2021 ). ( Negi et al, 2021 ) 263 International Journal of Public Sector Management Journal of Academic Librarianship Transnational Marketing Journal Journal of Public Affairs Sustainability (Switzerland) Organizational Dynamics Indian Journal of Forensic Medicine and Toxicology Journal of International Women's Studies International Journal of Disaster Risk Reduction Humanities and Social Sciences Letters Asian Social Work and Policy Review Work stress ( Molino et al, 2020 ), ( George, Atwater, Maneethai, & Madera, 2022 ), ( Joshi et al, 2020 ), ( Wiradendi Wolor et al, 2021 ), ( Subha et al, 2021 ; Syed et al, 2021 ) Work-life balance ( Wiradendi Wolor et al, 2021 ), ( Palumbo, 2020 ), ( Jasrotia & Meena, 2021 ), ( Subha et al, 2021 ) Purple ...…”
Section: Results and Findingsmentioning
confidence: 99%
“…Productivity : Research has found that productivity increases due to WFH ( Danker et al, 2022 ; Feng & Savani, 2020 ; Stoker et al, 2022 ; Tanpipat et al, 2021 ; Wiradendi Wolor et al, 2021 ). This is due to low-stress levels, managerial support ( Danker et al, 2022 ), changes in leadership behavior ( Stoker et al, 2022 ), high job motivation, norms in remote working ( Tanpipat et al, 2021 ), and increased work-life balance ( Wiradendi Wolor et al, 2021 ). Besides, one study found that WFH harms productivity ( Beno & Hvorecky, 2021 ).…”
Section: Results and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showing that working conditions do not have a significant impact on work-life balance is surprising, compared to previous studies carried out. Since Wolor, Nurkhin and Citriadin [ 48 ] have identified in a study in Indonesian context that having the right conditions while WFH does have a significant impact on work-life balance. A study conducted in Japan by Bannai and Tamakoshi [ 19 ] claim that higher working hours would result in an imbalance of work and life.…”
Section: Discussionmentioning
confidence: 99%